The Washington Peace Agreement and the U.S. Policy towards Ending the Civil War in the Kurdistan Region : (1998) - Mabast Hazhar Hamad; Sarwar Abdulrahman Omar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
In September 1998, Barzani and Talabani signed the U.S. mediated Washington peace agreement establishing a formal peace treaty. In the agreement, the parties agreed to share revenue, share power, deny the use of northern Iraq to the PKK, and not allow Iraqi troops into the Kurdish region. The United States pledged to use military force to protect the Kurds from possible aggression by Saddam Hussein. This study focuses on the U.S. policy towards resolving and ending the Kurdish civil war in Iraqi Kurdistan, which lasted after four years and directed the Kurdish question in Iraq into uncertain and harmful direction. Thousands of Kurdish citizens became victims of these internal battles. The agreement had a direct impact on the resolution of the military conflict between the two Kurdish parties, and became an important turning point in contemporary Kurdish history and gave the Kurdish leadership the opportunity to open a new chapter in dealing with each other. The agreement also led to a new policy in the region at the regional and international levels, in which the United States was able to prevent further political interference of the Ba'ath regime and neighboring countries in the affairs of the Kurdish autonomous region.